Assessment of cassava genotypes for resistance to cassava mosaic disease, cassava bacterial blight and cassava green mite at a lowland and mid-altitude site in Nigeria - Akparobi, S.O.; Togun, A.O.; Ekanayake, I.J. (African Journals Online, 1998)
Twelve cassava genotypes were evaluated in the field in two cropping seasons at two locations in Nigeria for their reaction to cassava mosaic disease (CMD), cassava bacterial blight (CBB) and cassava green mite (CGM), using visual injury scores as the index for resistance. Lowest indices for CMD were recorded at mid-altitude and were significantly different from lowland savanna indices. The highest injury scores for CMD, CBB and CGM were recorded 9 months after planting (MAP) which coincided with the dry period at both locations. TMS 30001 and TME1 showed resistance to CMD while TMS 30001, TMS 30572 and TMS 91934 were the most resistant to CBB. TME1, TMS 91934, TMS 30572 and TMS 50395 were moderately resistant to CGM. Leaf area and root yield of genotypes grown at the lowland site were higher than at mid-altitude. Genotypes with least leaf area and root yield had the highest injury scores for CMD and CBB in both locations. There was a significant positive correlation between CBB and CGM while a negative correlation was observed between root yield and CMD. Results suggest that selection for resistance to CBB may help breeders to develop cultivars resistant to CGM, and that CMD causes serious loss in cassava yields.